Estimation of inhibitory effect against tyrosinase activity through homology modeling and molecular docking - Daungkamon Nokinsee (2018)
© 2015 Daungkamon Nokinsee et al. Tyrosinase is a key enzyme in melanogenesis. Generally, mushroom tyrosinase from A. bisporus had been used as a model in skin-whitening agent tests employed in the cosmetic industry. The recently obtained crystal structure of bacterial tyrosinase from B. megaterium has high similarity (33.5%) to the human enzyme and thus it was used as a template for constructing of the human model. Binding of tyrosinase to a series of its inhibitors was simulated by automated docking calculations. Docking and MD simulation results suggested that N81, N260, H263, and M280 are involved in the binding of inhibitors to mushroom tyrosinase. E195 and H208 are important residues in bacterial tyrosinase, while E230, S245, N249, H252, V262, and S265 bind to inhibitors and are important in forming pi interaction in human tyrosinase.